Analisis Faktor-Faktor yang Mempengaruhi Penyerapan Anggaran di Sekretariat Daerah Kabupaten Mimika - Yundy Hafizrianda; Vatreane (Universitas Cenderawasih, 2025)
This study aims to analyze the influence of budget planning, budget implementation, and monitoring and evaluation on the level of budget absorption in the Mimika Regency Regional Secretariat. The problem of low budget absorption that often occurs at the end of the fiscal year is an important background, because it can cause suboptimal utilization of public funds and hinder the achievement of development targets. The research method used is a descriptive quantitative method with a survey approach through a questionnaire. The population in this study were all employees of the Mimika Regency Regional Secretariat involved in the process of budget planning, implementation, and monitoring. Data analysis was carried out using multiple linear regression analysis to test the effect of independent variables on the dependent variable. The R-Square (R²) on the Budget Absorption variable (Y) of 0.786 indicates that 78.6% of the variation in budget absorption can be explained by three independent variables, namely Budget Planning (X1), Budget Implementation (X2), and Monitoring & Evaluation (X3). The Adjusted R-Square value (0.765) which is close to R² indicates that the model does not experience overfitting, so that the three variables collectively have a significant influence on budget absorption. Theoretically, this research strengthens the literature in the field of public financial management, particularly regarding performance-based management models and the principles of good governance. Practically, the research findings provide recommendations for local governments to improve planning systems, increase implementation capacity, and strengthen oversight to promote effective regional budget utilization. Keywords: Budget Absorption, Regional Secretariat